Integrating Project-based Activity in Improving the Science Academic Performance of Learners in the New Normal - Solis, Jeanette Mamaril (Future Science / FSH-PH Publications, 2021)
The objective of this paper was to determine the efficacy of Project-based learning in increasing the academic performance of learners in remote learning amidst the pandemic. There were eight (8) Project-based instructional activities across six (6) most essential learning competencies in Earth Science were included in the Grade 9 Unit three Earth Science. The computed t value of 5.08 is greater than the t critical value of 2.0049 at level of significance of 0.05, the statistical decision is to reject the null hypothesis. There is a significant difference between the pre-test and post-test of the respondents who were subjected to project-based activity. Result implied that there is enough evidence to support the claim that integrating project-based activity can effectively improve the academic performance of the respondents. Based on the analysis gathered by the researcher, the use of project-based activity in on-line teaching is highly effective in improving the academic performance of students in Earth Science. Therefore, I, the researcher, recommends the use of project-based method of teaching in the on-line distance learning.